Security Authentication Framework Design for Electric Internet of Things. Issue 1 (1st October 2022) - Song, Weiqiong; Guo, Shuai; Li, Jiwei; Liu, Heng; Wu, Zaijun; He, Xiaorong; Hou, Yunyang
Abstract : The intelligent terminal equipment of the electric internet of things (IoT) is vulnerable to network attacks when installing APPs from the application store. Encryption of the communication process can enhance security protection, but the key needs to be stored in the local equipment. When the equipment is attacked, the key is leaked easily resulting in communication security problems. To solve the above problems, we proposes a terminal APP security authentication mechanism based on TrustZone approach and OP-TEE (Open Source Trust Execution Environment) system to identify the identity information of both sides of the communication. The digital certificate of the application store is checked before the terminal equipment installs the APP. After the check is passed, the session key is generated in the Trusted Execution Environment (TEE), and the communication parties use the session key to encrypt the subsequent process. Simulation results validate that the proposed security authentication mechanism can effectively protect the communication process of terminal equipment installation APP and meet the performance requirements.